If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (X + 4)(5x + -6) = 0 Reorder the terms: (4 + X)(5x + -6) = 0 Reorder the terms: (4 + X)(-6 + 5x) = 0 Multiply (4 + X) * (-6 + 5x) (4(-6 + 5x) + X(-6 + 5x)) = 0 ((-6 * 4 + 5x * 4) + X(-6 + 5x)) = 0 ((-24 + 20x) + X(-6 + 5x)) = 0 (-24 + 20x + (-6 * X + 5x * X)) = 0 (-24 + 20x + (-6X + 5xX)) = 0 Reorder the terms: (-24 + -6X + 20x + 5xX) = 0 (-24 + -6X + 20x + 5xX) = 0 Solving -24 + -6X + 20x + 5xX = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '24' to each side of the equation. -24 + -6X + 20x + 24 + 5xX = 0 + 24 Reorder the terms: -24 + 24 + -6X + 20x + 5xX = 0 + 24 Combine like terms: -24 + 24 = 0 0 + -6X + 20x + 5xX = 0 + 24 -6X + 20x + 5xX = 0 + 24 Combine like terms: 0 + 24 = 24 -6X + 20x + 5xX = 24 Add '-20x' to each side of the equation. -6X + 20x + -20x + 5xX = 24 + -20x Combine like terms: 20x + -20x = 0 -6X + 0 + 5xX = 24 + -20x -6X + 5xX = 24 + -20x Reorder the terms: -24 + -6X + 20x + 5xX = 24 + -20x + -24 + 20x Reorder the terms: -24 + -6X + 20x + 5xX = 24 + -24 + -20x + 20x Combine like terms: 24 + -24 = 0 -24 + -6X + 20x + 5xX = 0 + -20x + 20x -24 + -6X + 20x + 5xX = -20x + 20x Combine like terms: -20x + 20x = 0 -24 + -6X + 20x + 5xX = 0 The solution to this equation could not be determined.
| kx^2+12+k=0 | | x+45=56 | | -r=-12 | | 2(6-x)=-2(4-x) | | 9(x-3)=2(2x+9) | | x^4+2x^3-3x^2-36x=0 | | 6*(4-x)+6x=24 | | 32-5x=20-3x | | x-1+12=7x-25 | | 4x-6=5x-6 | | x+0.833(x)=7791.56 | | 3x^3+x=4x^2 | | 3x-2(6x-3)=42 | | 53+2x=18-3x | | 149-6x=6x+7 | | 7y+3x=20 | | 38-3x=23 | | 3(2x+5)=-3(-3x-2) | | 9x-5=5x-17 | | x+9=-5x+3 | | 56-2x=9x+25 | | 3x+6=10x-15 | | 2x(x-3)=7(x-3) | | 7s-4=26 | | x+0.833*x=7791.56 | | 2(3x-1)+3=21 | | 2x+40-6x=2-9x+3 | | 2x^2+54x=18 | | 3x-42=5x | | 8x+7x-54=180 | | 3x+3=12x-40 | | 2x^2+27x=9 |